(untitled) (Journal of Medical & Health Sciences Review, 2025)
Abstract In the fast-growing world, dielectric materials with high energy storage density temperature stability, and low loss are eagerly desired for advanced pulsed capacitors applications. The basic principles of dielectric energy storage and the factors affecting energy storage density are introduced. The research progress of glass-type high-energy storage materials, ferroelectric glass-ceramics-type high-energy storage materials, ferroelectric-anti-ferroelectric ceramics, and ferroelectric polymer-type high-energy storage materials are reviewed. For an ideal or good energy storage material their Curie temperature should be high, high dielectric constant, and have strong saturation polarization.